AL IMAM JALAL AL-DIN AL-SUYUTI (T: 911 e) And His VERBAL INCREASES On The BOOK (COLLECTION Of MOSQUES) IMAM TAJ AL-DIN AL-SABKI (v: 779 e) In His BOOK (BRIGHT PLANET SYSTEMS COLLECTION Of MOSQUES ) - KHALAF , OTHMAN; MAJEED , FIRAS (Islamic Sciences Journal, 2023)
This research is concerned with the science of the origins of beliefs, which is one of the greatest religious sciences and the highest of its rank And going into it is one of the most noble and greatest projects that will achieve the death of life for its sake and searched for it in the verbal increases of Imam Al-Suyuti that he added to the book collecting mosques for Imam al-Sibki and studying them to increase interest.